Komunikasi Pemerintah Dalam Membangun Moderasi Beragama Berbasis Nilai Kearifan Lokal di Kota Tanjung Balai - Mailin; Lahmuddin; Waris (JURNAL PENELITIAN, 2023)
The objective of this study is to examine the government's communication strategies in building religious moderation in Tanjung Balai City. This research holds significance due to the historical prevalence of intolerance instances in the city of Tanjungbalai, earning it the reputation as one of the places with a high level of intolerance. Tanjung Balai possesses a rich historical heritage of local wisdom that might serve as a means to promote religious moderation within the community. This study employs a qualitative research methodology utilizing a phenomenological approach. The data collection techniques employed in this article are observation, interviews, and documentation. Then, the collected data will be analyzed. The obtained data will undergo analysis employing qualitative research methods.  The research findings indicate that the city of Tanjung Balai is currently rich in ethnic and religious diversity. This city possesses a distinctive cultural background due to the presence of multiple communities that still adhere to animism and dynamism. Local knowledge can be effectively utilized to combat intolerance by promoting unity and setting aside differences. Currently, the government has been advocating for the utilization of local knowledge as a means to achieve religious moderation. However, the extent of its effectiveness has not yet been measured. At this level, it is necessary for the government to actively collaborate and create synergy with the community in order to mitigate religious issues in the city of Tanjung Balai.